2001
DOI: 10.1111/1467-9280.00317
|View full text |Cite
|
Sign up to set email alerts
|

Changing Faces: A Detection Advantage in the Flicker Paradigm

Abstract: Observers seem surprisingly poor at detecting changes in images following a large transient or flicker. In this study, we compared this change blindness phenomenon between human faces and other common objects (e.g., clothes). We found that changes were detected far more rapidly and accurately in faces than in other objects. This advantage for faces, however, was found only for upright faces in multiple-object arrays, and was completely eliminated when displays showed one photograph only or when the pictures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
241
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(272 citation statements)
references
References 21 publications
27
241
2
Order By: Relevance
“…5.1 Detection rates and resistance of facial stimuli to IB Experiment 1 showed that faces are significantly better detected than pictures of common objects (58% versus 4% of detection) under condition of inattention, confirming, with more realistic stimuli, previous findings about the special attentional properties of faces (Mack and Rock 1998;Ro et al 2001;Theeuwes and Van der Stigchel 2006; but see Palermo and Rhodes 2003). In addition, the results of experiment 2 showed that upright faces are also better detected than inverted faces (50% versus 20% of detection), ruling out any alternative explanation in terms of potential low-level inherent differences between faces and objects.…”
Section: Discussionsupporting
confidence: 77%
“…5.1 Detection rates and resistance of facial stimuli to IB Experiment 1 showed that faces are significantly better detected than pictures of common objects (58% versus 4% of detection) under condition of inattention, confirming, with more realistic stimuli, previous findings about the special attentional properties of faces (Mack and Rock 1998;Ro et al 2001;Theeuwes and Van der Stigchel 2006; but see Palermo and Rhodes 2003). In addition, the results of experiment 2 showed that upright faces are also better detected than inverted faces (50% versus 20% of detection), ruling out any alternative explanation in terms of potential low-level inherent differences between faces and objects.…”
Section: Discussionsupporting
confidence: 77%
“…Note that in the current study it is critical that we examined whether one's own face would be prioritized among other faces. Previous studies have already established that a face among non-face objects receive attentional priority (e.g., Ro, Russell, & Lavie, 2001;Theeuwes & Van der Stigchel, 2006). In the current study we asked the question whether the features that make up your own face would receive priority over faces which do not contain one's own facial features.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that people often fail to notice changes in objects that occupy their visual field-even seemingly obvious changes-unless they specifically allocate attention to that object (for a vivid example, see Simons & Levin, 1998.). Change-detection methods have been used successfully in past research documenting allocation of attention to functionally important social objects (Ro et al, 2001;Davies & Hoffman, 2002). In the present study, we employed a change-detection task designed to assess the extent to which participants selectively allocated attention to attractive (versus unattractive) opposite-sex and same-sex others -all of whom were present simultaneously in the perceptual environment.…”
Section: Change Detection As a Means Of Measuring Selective Allocatiomentioning
confidence: 99%